Peningkatan Tata Kelola pada Sistem Manajemen Persediaan melalui Edukasi dan Pelatihan bagi UMKM di Desa Wisata Wates Jaya, Kabupaten Bogor - Muliani, Lila; Suprayitno, Degdo; Hidayat, Yusup Rachmat (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as one of the pillars of the national economy and provide significant employment opportunities. MSMEs located in tourist villages also play a crucial role. In the tourism sector, tourist villages also act as key drivers of economic growth. Therefore, MSMEs and tourist villages are interconnected in a mutually reinforcing relationship. In the tourism activity framework known as the 3S concept (something to see, something to do, something to buy), MSMEs serve as the primary actors in the "something to buy" aspect. Wates Jaya Tourist Village, located in Bogor Regency, is an emerging tourist destination. Apart from issues related to capital and marketing, MSME entrepreneurs in Wates Jaya Village face challenges in raw material supply, cost of goods sold (COGS) calculations, and suboptimal record-keeping or administrative management. Training programs have been conducted to address these challenges by developing an integrated inventory management system that facilitates calculation and record-keeping through simple digital technology. However, evaluation results indicate that regular mentoring is still needed to enhance MSMEs' proficiency in utilizing the system effectively.